Returns to Returning: Who Went Abroad and What Does it Matter? - Catherine Y. Co; Myeong-Su Yun; Ira N. Gang (Institute for the Study of Labor (IZA), 1998)
We examine the labor market performance of return migrants using the Hungarian Household Panel Survey. Two distinct selection issues are considered in the estimation of the earnings equation. The result that there is a ?premium? to work experience abroad for women is robust across models we considered. This premium varies by former host country. For men, the return to working abroad is not generally significant, except for those Hungarians who worked in non-European OECD countries.
Keywords: J24; J61; F22; 330; return migration; earnings; human capital; Lohn; Rückwanderung; Ungarn